KASUS KELAHIRAN YANG TIDAK DIINGINKAN DI DAERAH ISTIMEWA YOGYAKARTA ANALISIS DATA SDKI 1991 - Helly Prajitno Soetjipto; Sukamdi Sukamdi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1993)
This study is intended to pursue the previous attempts in examining the relationship between low fertility regime and the case of births which had been delivered unintendedly in Yogyakarta. Using an unweighted sample of 575 married women in the Indonesian Demographic and Health Survey 1991, this study found that 75 cases out of 474 last birth children were bom unintendedly (beyond the range of ideal number of children). Most of the 75 cases were bom by women who have 2 or 3 ideal number of children and by a devoted Family Planning acceptors. Most of the women have limited accesses in education and economic activities. The case of unwantednes were found predominantly among women older than 25 years. Even though only a tentative findings, this study shed some light to the fact that Family Planning program to some extent may contribute to the rate of unwantedness. Apolicy is needed especially in reducing the risk of unwantedness among the low-income women.